Severity of imported malaria: protective effect of taking malaria chemoprophylaxis - Vliegenthart-Jongbloed, Klaske (BioMed Central, 2013)
BACKGROUND: Although chemoprophylaxis remains an important strategy for preventing malaria in travellers, its effectiveness may be compromised by lack of adherence. Inappropriate use of chemoprophylaxis is likely to increase the risk of acquiring malaria, but may probably also worsen the severity of imported cases. The aim of this study was to assess the impact of use of malaria chemoprophylaxis on clinical features and outcome of imported malaria. METHODS: Demographic, clinical and laboratory data of patients included in the Rotterdam Malaria Cohort between 1998 and 2011 were systematically collected and analysed. Patients were classified as self-reported compliant or non-compliant users or as non-users of chemoprophylaxis. Severe malaria was defined using the 2010 WHO criteria. RESULTS: Details on chemoprophylaxis were available for 559 of the 604 patients, of which 64.6% were non-users, 17.9% were inadequate users and 17.5% reported to be adequate users. The group of non-users was predominated by patients with African ethnicity, partial immunity and people visiting friends and relatives. The majority contracted Plasmodium falciparum malaria. In contrast, compliant users acquired non-falciparum malaria more frequently, had significant lower P. falciparum loads on admission, shorter duration of hospitalization and significant lower odds for severe malaria as compared with non-users. Patients with P. falciparum malaria were more likely to have taken their chemoprophylaxis less compliantly than those infected with non-P. falciparum species. Multivariate analysis showed that self-reported adequate prophylaxis and being a partially immune traveller visiting friends and relatives was associated with significantly lower odds ratio of severe malaria. In contrast, age, acquisition of malaria in West-Africa and being a non-immune tourist increased their risk significantly. CONCLUSIONS: Compliant use of malaria chemoprophylaxis was associated with significantly lower odds ratios for severe malaria as compared with non-compliant users and non-users of chemoprophylaxis. After correction for age, gender and immunity, this protective effect of malaria chemoprophylaxis was present only in individuals who adhered compliantly to use of chemoprophylaxis. Patients with P. falciparum malaria were more likely to have used their chemoprophylaxis less compliantly than patients with non-P. falciparum malaria who were more likely to have contracted malaria in spite of compliant use of chemoprophylaxis.